Elements of pronunciation : Intensive practice for intermediate and more advanced students - Mortimer, Colin. (Nxb Tp.HCM, 2001)
Key to phonetic symbols; To the student; To the teacher; Weak forms; Clusters; Link-up; Contractions; Stress time.